Small Claim Court as a Refund State Losses Due to Corruption Crime By State Attorney - Sri Wulan Hadjar; Osgar Sahim Matompo; Irmawaty (Indonesian Research Journal in Legal Studies, 2022)
This study aims: (1) To find out the legal remedies taken by the prosecutor against the return of state losses in the crime of corruption. (2) The Effectiveness of the Prosecutors' Efforts as State Lawyers in Recovering State Losses Due to Corruption Crimes. The method that the researcher uses in writing this thesis is using a normative juridical research approach. Research Results: (1). The settlement of civil cases through the small claim court at the District Court is very helpful for the community to resolve their cases in a simple, fast, and low cost way. Perma No. 2 of 2015 and Perma No. 4 of 2019 is a new breakthrough and fills the legal vacuum to resolve simple cases that were previously resolved normally. (2). The limitation on the material value of the lawsuit is Rp. 500,000,000 (five hundred million rupiah) for example, which means that if the lawsuit filed exceeds this value, the lawsuit will not be accepted for settlement through a simple lawsuit process. Research Suggestions: (2) For litigants, it is hoped that they will be able to comply with and follow all the regulations in the Court, especially during the case examination process. Because the litigants actually also have an important role in the creation of a judiciary that is simple, fast, and low-cost as expected. (2). The Court must provide legal counseling by cooperating with related agencies (kelurahan and city governments) to the general public, so that public awareness of the law can be realized. So as a result it does not become one of the obstacles in the judicial process which is simple, fast, and low cost.